2003
DOI: 10.1210/jc.2002-021960
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Tissue Selectivity of the Synthetic Androgen 7α-Methyl-19-Nortestosterone in Hypogonadal Men

Abstract: The potent synthetic androgen 7 alpha-methyl-19-nortestosterone (MENT) is resistant to 5 alpha-reductase but is a substrate for aromatase. It may therefore offer selective sparing of the prostate gland while supporting other androgen-dependent tissues. MENT acetate implants were administered for 24 wk to 16 hypogonadal men, randomly allocated to 1 or 2 implants (groups I and II, respectively; releasing approximately 400 microg/d x implant). Hemoglobin concentration and hematocrit were maintained during MENT tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 72 publications
4
44
0
1
Order By: Relevance
“…A comparative study (68) shows that the MENT implants were well tolerated and preferred to the frequent injection of testosterone enanthate. A recent abstract showed a decrease in prostate volume while muscle mass increased (69). More data are needed for further evaluation of the clinical effects and long-term safety of MENT, in particular on plasma lipids.…”
Section: Choice Of Testosterone Preparationmentioning
confidence: 99%
“…A comparative study (68) shows that the MENT implants were well tolerated and preferred to the frequent injection of testosterone enanthate. A recent abstract showed a decrease in prostate volume while muscle mass increased (69). More data are needed for further evaluation of the clinical effects and long-term safety of MENT, in particular on plasma lipids.…”
Section: Choice Of Testosterone Preparationmentioning
confidence: 99%
“…Indeed, in contrast to testosterone, MENT is less potent on male accessory sex glands compared with its ability to suppress gonadotropins; MENT otherwise can be aromatized to 7a-methyl-E 2 (LaMorte et al 1994). These observations indicate that MENT, as a component for androgen replacement therapy or male contraceptive, has health-promoting effects, particularly by avoiding hyperstimulative effects on the prostate, including prostatespecific antigen (Kumar et al 1992, Morali et al 1993, Cummings et al 1998, Anderson et al 2003, von Eckardstein et al 2003, Walton et al 2007, and those derived from MENT aromatization (LaMorte et al 1994, Anderson et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Anderson et al [21] demonstrated a significant decrease in BMD at the lumbar spine when hypogonadal men were administered with 7␣-methyl-19-nortestosterone (MENT), while testosterone treatment demonstrated no significant change but maintained the lumbar spine BMD. MENT is a potent synthetic androgen that is resistant to 5␣-reduction, but can be converted by the aromatase to an active estrogen [22].…”
Section: Discussionmentioning
confidence: 99%